1989
DOI: 10.1128/aem.55.2.433-439.1989
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the Anaerobic Biodegradation Potential of Organic Chemicals in Digesting Sludge

Abstract: The degradation potential of 77 organic chemicals under methanogenic conditions was examined with an anaerobic digesting sludge from the United Kingdom. Degradation was assessed in terms of net total gas (CH4 plus C02) produced, expressed as a percentage of the theoretical production (ThGP). The compounds tested were selected from various chemical groups and included substituted phenols and benzoates, pesticides, phthalic acid esters, homocyclic and heterocyclic ring compounds, glycols, and monosubstituted ben… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(41 citation statements)
references
References 25 publications
3
37
0
1
Order By: Relevance
“…Abiotic transformation of 2nitrophenol and 2,4-dinitrophenol, under reducing conditions (with sulfide or cysteine), has also been reported by Gorontzy et al (1993). Biological degradation of 4-nitrophenol confirms the findings of other researchers (Horowitz et al, 1982;Boyd et al, 1983;Battersby and Wilson, 1989;Haghighi et al, 1995).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Abiotic transformation of 2nitrophenol and 2,4-dinitrophenol, under reducing conditions (with sulfide or cysteine), has also been reported by Gorontzy et al (1993). Biological degradation of 4-nitrophenol confirms the findings of other researchers (Horowitz et al, 1982;Boyd et al, 1983;Battersby and Wilson, 1989;Haghighi et al, 1995).…”
Section: Resultssupporting
confidence: 88%
“…In (1995) and Sluder (1994). Battersby and Wilson (1989) reported that 2-nitrophenol was not inhibitory while 4-nitrophej:…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Aftring et al, showed that phthalate isomers can be degraded under anoxic conditions (Aftring et al, 1981). Although less understood than aerobic phthalate degradation, anaerobic degradation of phthalate isomers and phthalate esters was reported for numerous pure and mixed cultures under nitrate-or sulfate-reducing or methanogenic conditions (Battersby and Wilson, 1989;Kleerebezem et al, 1999;Qiu et al, 2006;Cheung et al, 2007;Liang et al, 2008), but no decisive studies on the degradation pathways have been published so far.…”
Section: Introductionmentioning
confidence: 99%
“…The preliminary anaerobic contact stage served to equalize and partially degrade the raw compounds. Such an environment has been reported to facilitate subsequent aerobic degradation by transforming complex organic compounds into readily degradable molecules (Young, 1981 ;Battersby and Wilson, 1989). At the beginning of the study, a screening system composed of four reactors in series (two anaerobic and two aerobic) was operated for several months with no attempt at sludge concentration.…”
Section: Biological Treatability Of Complex Chemical Wastewatermentioning
confidence: 99%